Using Songs in an English Language Teaching Classroom - Andrew, Yau-hau Tse (2012)
All English courses have a fixed curriculum (eg, grammatical items to be learnt and taught) and teaching materials (eg, handouts, videos, and audios). Many teachers still base their teaching on grammar rules, rote learning, and textbook-bound lectures. Students find English classrooms impractical and boring. Rarely teachers use other means to motivate students to learn English. The use of songs as a means to teach English is not widespread, but neither is it rare. The objective of this workshop is twofold: a) to introduce the use of English songs in a language learning classroom; and b) to help language teachers teach the four language skills, ie, listening, speaking, reading, and writing via songs. At the end of this workshop, participants are expected to: i) recognize the importance and usefulness of using songs in the classroom; and ii) find appropriate songs to aid teaching and devise appropriate learning tasks, via English songs, for their students. To conclude, the rationale for running the workshop is to aware the participants of the current pedagogy in using songs in English language teaching and learning resulting in motivating their students to learn English and enhancing their language proficiency and competency